2001
DOI: 10.1200/jco.2001.19.2.432
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Endothelial Growth Factor 189 mRNA Isoform Expression Specifically Correlates With Tumor Angiogenesis, Patient Survival, and Postoperative Relapse in Non–Small-Cell Lung Cancer

Abstract: The VEGF189 mRNA isoform expression ratio shows a greater correlation with tumor angiogenesis, postoperative relapse time, and survival than do the expression ratios for the VEGF121, VEGF165, and VEGF206 mRNA isoforms and can be used as a prognostic indicator for patients with non-small-cell lung cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
115
0
2

Year Published

2002
2002
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(123 citation statements)
references
References 28 publications
6
115
0
2
Order By: Relevance
“…This suggests that two subtypes of WT may be defined according to WT1 and VEGF expression. The observation of VEGF underexpression in most tumours contrasts with the frequent observation of VEGF overexpression in various tumours, which is correlated with a poor prognosis (Linderholm et al, 2001;Yuan et al, 2001). Overexpression of VEGF was observed in only six tumours and all these patients are alive without relapse, with a follow-up of at least 6 years.…”
Section: Discussionmentioning
confidence: 80%
“…This suggests that two subtypes of WT may be defined according to WT1 and VEGF expression. The observation of VEGF underexpression in most tumours contrasts with the frequent observation of VEGF overexpression in various tumours, which is correlated with a poor prognosis (Linderholm et al, 2001;Yuan et al, 2001). Overexpression of VEGF was observed in only six tumours and all these patients are alive without relapse, with a follow-up of at least 6 years.…”
Section: Discussionmentioning
confidence: 80%
“…Vascular endothelial growth factor (VEGF) and the plateletderived growth factor (PDGF) signalling pathways are critical components in the pathogenesis of non-small cell lung cancer (NSCLC) (Koukourakis et al, 1997;Yuan et al, 2001;Shikada et al, 2005). Clinical data with the anti-VEGF monoclonal antibody, bevacizumab, plus first-line chemotherapy improved efficacy in patients with advanced NSCLC (Sandler et al, 2006;Manegold et al, 2007Manegold et al, , 2008, indicating that targeting angiogenesis through VEGF is a viable strategy.…”
mentioning
confidence: 99%
“…Not only is VEGF a diffusible endothelium-specific mitogen and angiogenic factor, it also increases vascular permeability [5] and stimulates/maintains neovascularisation in a variety of tumour types [20]. Indeed, enhanced VEGF gene expression has been identified in a number of malignant tumours from breast, lung, ovarian, liver, and colon cancer in comparison with normal tissue [6][7][8][9][10]. Unfortunately, there were few conclusive studies on the correlations of VEGF expression and osteosarcoma, except some that showed osteosarcoma patients who expressed high levels of VEGF but exhibited a poorer prognosis [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…Vascular endothelial growth factor (VEGF) is a major angiogenic factor that induces endothelial cell proliferation and increases the permeability of the vascular endothelium [4,5]. Enhanced VEGF gene expression has been reported in primary tumours from breast, lung, ovary, liver and colon [6][7][8][9][10]. In comparison with other types of cancers, there were limited clinical reports in the orthopaedic literature search that suggested the correlation of high VEGF and poor prognosis in osteosarcoma [11].…”
Section: Introductionmentioning
confidence: 99%